2019
DOI: 10.1111/nep.13528
|View full text |Cite
|
Sign up to set email alerts
|

Kidney biopsy in the elderly: Safety and strategies to prevent uremic bleeding

Abstract: Categorical variables are expressed as n (%) and compared using χ 2 test. ‡ Bonferroni correction was performed for multiple comparisons; hence, difference was considered significant if P value was <0.0167.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…As previously reported in multiple studies [12][13][14][15][16], the percentage of elderly patients undergoing renal biopsy, over the years, has increased in our center. Among elderly and non-elderly patients with renal disease, the risk of undergoing renal biopsy is comparable [6,17]. In addition, nephrologists may be more willing to perform biopsy in elderly patients in recent years compared to the past.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported in multiple studies [12][13][14][15][16], the percentage of elderly patients undergoing renal biopsy, over the years, has increased in our center. Among elderly and non-elderly patients with renal disease, the risk of undergoing renal biopsy is comparable [6,17]. In addition, nephrologists may be more willing to perform biopsy in elderly patients in recent years compared to the past.…”
Section: Discussionmentioning
confidence: 99%
“…While it was possible that voluntary participation may result in selection bias if nonresponders rejected the study because they had vaccine hesitancy, we found that vaccine uptake was not different between nonresponders and responders. The HLS-EU-47 questionnaire was intended to be self-administered but we adapted its administration to a telephone interview due to a move toward teleconsultations during the pandemic with reduced in-person clinic visits, while electronic mail or online self-administered surveys may result in even lower response rates since our patients with glomerulonephritis are increasingly older and some may be less adept using these technology [ 26 ]. Although few socioeconomic status measures differentiated health literacy in this cohort, this may be due to the predominantly middle-class nature of the cohort with few patients in the extremities of the socioeconomic status spectrum, thus limiting the ability to detect significant associations with health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…As patients undergoing kidney biopsy are increasingly older and older age is associated with higher red cell transfusion rates after percutaneous kidney biopsy, 2,24 pre‐biopsy DDAVP in selected cases may be beneficial in reducing bleeding complications in addition to standard precautions. While the Swedish cohort tended to be older (desmopressin group: mean age 55.6 ± 16.6 years; no desmopressin group: 58.5 ± 17 years), Manno et al .…”
Section: Discussionmentioning
confidence: 99%